The use of spatial manipulation to examine goalkeepers` anticipation - Woolley, T. L.; Crowther, R. G.; Doma, K.; Connor, J. D. (Journal of Sports Sciences, 2015)
This study investigated whether anticipation and search strategies of goalkeepers are influenced by temporally and spatially manipulated video of a penalty. Participants were clustered into three groups depending on skill: goalkeepers (n = 17), field players (n = 20) and control group (n = 20). An eye tracker was worn whilst watching 40 videos of a striker kicking to four corners of a goal in random order. All 40 videos were temporally occluded at foot-to-ball contact, and the non-kicking leg of 20 videos was spatially manipulated. Results showed that goalkeepers had significantly better predictions than the two groups with no differences between the two testing conditions. According to effect size, the percentage of fixation location and viewing time of the kicking leg and ball were greater for the goalkeepers and field players group than the control group irrespective of testing conditions. The fixations on the kicking leg and ball in conjunction with comparable predictions between spatially manipulated and control conditions suggest that goalkeepers may not rely on the non-kicking leg. Furthermore, goalkeepers appear to use a global perceptual approach by anchoring on a distal fixation point/s of the penalty taker whilst using peripheral vision to obtain additional information.